Ultrassonografia de glândulas genitais acessórias em carneiros da raça Dorper: caracterização e correlações reprodutivas - Camela, Efigénia Singa Cassule [UNESP] (2015)
This study aimed to characterize and describe the ultrassonographic parameters of prostate, vesicular, bulbourethral glands and Doppler vascular index of testicular arteries and internal iliac of Dorper rams, correlating them with evaluation of testicles, semen and serum testosterone levels according to the animals sexual maturity. We evaluated 45 animals: 24 pubescent (8 and 11 months) and 21 mature (≥ 12 months) of age. Males were examined by ultrasound before and after semen collection and seminal glands were biometric measured. We conducted qualitative analysis of accessory glands by the echotexture (homogenitys and heterogenety) and echogenicity (hypo/hyperechoic high and low intensity and anechogenic). Semen had it morphological and physiological characteristics evaluated. Vesicular and bulbourethral glands were found to have a heterogeneous echotexture, predominantly hypoechoic echogenicity of low intensity. The prostate gland parenchyma presented with homogeneous echo texture compared to other glands and hypoechoic echogenicity. The values for age 8-11 months were: vesicular gland (24.81±3.26 mm); Prostate (12.88±1.20 mm); and bulbourethral (13.72±1.31 mm). The values for animals> 12 months were: vesicular glands (24.58±3.77 mm); Prostate (14.22±2.67 mm); and bulbourethral (14.71±1.78 mm). There were significant correlations (p<0.05) for the dimensions of the accessory genital glands with testicles, seminal characteristics and testosterone serum levels. It is concluded that the conventional ultrasound of the vesicular and bulbourethral glands have heterogeneous echo texture, predominantly hypoechoic echogenicity of low intensity regardless of age. The prostate gland has the parenchyma with more homogeneous echo texture and echogenicity shows up high intensity hypoechoic in the dorsal part of the urethra and of low intensity hypoechoic in the ventral part to the urethra. Mature Dorper rans, showed higher dimensions ...